Menggali Kreativitas Mahasiswa dalam Memahami Lingkungan Berkelanjutan melalui Pembelajaran SSCS (Search, Solve Create and Share) - Sahabuddin, Erma Suryani (Universitas Negeri Makassar, 2024)
This research examines the importance of knowledge about environmental sustainability for prospective teachers, who will become educators for the young generation in elementary schools. The primary aim of this study is to describe the effectiveness of the Search, Solve, Create, and Share (SSCS) learning model in enhancing the understanding of environmental sustainability among Elementary School Teacher Education (ESTE) students. This qualitative descriptive research involved 35 ESTE students during the odd semester of 2023. Data were collected through observation, interviews, and documentation. The findings indicate that the implementation of the SSCS model significantly contributed to the improvement of students’ understanding of environmental sustainability. This learning model is recommended for adoption by educational institutions to enrich the learning process and prepare prospective teachers capable of educating students on the importance of maintaining environmental sustainability.